Spatio-Temporally Adaptive Waiting Time for Cell Phone Sensor Networks - Deepthi Chander; Bhushan Jagyasi; U. B. Desai; S. N. Merchant (International Journal of Distributed Sensor Networks)
In cell phone sensor networks (CpSN), sensor-embedded cell phones communicate sensor data using Near Field Communication outlets such as Wi-Fi or Bluetooth. This paper considers a query dissemination application of CpSN, where sensor data belonging to a certain time window [ t s , min , t s , max ] is needed from a region of interest. Existing approaches, such as ADAPT, use adaptive broadcast ranges at the Wireless Access Point (WAP) for query dissemination. This paper proposes the adaptation of waiting time at nodes for energy-efficient query dissemination. The design and analysis of the proposed Spatio-Temporally Adaptive Distributed Velocity Dependent (STA-DVD) waiting time is presented. The STA-DVD protocol is analytically compared with a Spatially Adaptive Distributed Velocity Dependent (SA-DVD) waiting time based protocol. Simulation results show that STA-DVD has a superior querying performance in terms of number of samples procured than SA-DVD, at a slightly higher energy cost. For the case of a Randomized Waiting (RW) time adopted by nodes in ADAPT, the ADAPT-RW protocol has the best querying performance, with significantly high energy costs. STA-DVD has a comparable querying performance with ADAPT-RW, for high residual times and a better performance for low residual times, with significantly low energy dissipation.